Sixth Five Year Plan 1980-85 A Framework - Planning Commission, Government of India (Planning Commission, Government of India, 1980)
A copy of the draft Plan-frame is attached. While formulating the Programme Thrusts, the 20-point economic programme and the pledges given to the people have also been among the principal guiding factors. The document Is not intended to be exhaustive covering all sectors of the economy but rather seeks to highlight as an approach paper the problems and programmes in a few key areas of the economy. Programmes relevant to all sectors of the economy are being worked out by the concerned Ministries in the Central Government and State Governments and these will be considered at the time of the preparation of the Draft Plan later in the year. It is important in designing the programmes for different sectors to build into the programmes adequate arrangements for their effective implementation.
Planning Commission
Planning Commission
Keywords: Sixth Five Year Plan- India; Economic Development of India; Human Resource Development; Industry and Infrastructure